Study on the effect of blood flow restriction training combined with IASTAM on ankle strength and function intervention in athletes with chronic ankle instability in sport dance events - Lui, Y.; Wang, Y. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Athletes engaged in sports dance frequently encounter the potential for ankle injuries and instability, factors that may contribute to diminished training efficacy, compromised athletic performance, prolonged recuperation, and heightened susceptibility to recurring injuries.